Theoretical Estimation of Optimal Linear Cooling Rate for PK-15 Cell Suspension - Gordienko, Olga; Kovalenko, Igor; Kovalenko, Svitlana; Kuleshova , Larysa; Todrin , Oleksandr (Problems of Cryobiology and Cryomedicine, 2021)
Preservation of cells during crystallization of the cell suspension is influenced by two types of damaging factors. The first type of cryoinjury occurs during the crystallization of the extracellular environment and is caused by dehydration of cells, increasing the concentration and ionic strength of extracellular and intracellular solutions. As the cooling rate rises, the damage rate of the first type decreases as a result of the reduced time of action of damaging factors. The second type of cryoinjury is intracellular crystallization, the probability of which enhances at high cooling rates, is considered the most destructive to cells. The optimal linear cooling rate for PK-15 cells is determined using a physico-mathematical model, which describes the probability of cryoinjury of cells in the linear freezing mode and is based on the two-factor theory of cryoinjury, thermodynamic theory of homogeneous crystallization and general theory of activation-type processes. The findings have shown that within the range of cooling rates < 0.5 °C/min the cryoinjury of PK-15 cells occurs mainly due to the effects of the solution, and at cooling rates > 2.5 °C/min this was mainly resulted from an intracellular crystallization. The dependence of the percentage of damaged cells on the cooling rate has a relatively wide minimum within the range of cooling rates of 0.5 °C/min… 2.5 °C/min. Probl Cryobiol Cryomed 2021; 31(3): 214-222